Foreword - Zigmunde, Alīda (History of Engineering Sciences and Institutions of Higher Education, 2019)
This is the third volume of the scientific journal of RTU Research Centre for Engineering History (RCEH). The articles in the journal mainly are reports from the 59th International Scientific Conference held on 10 October 2018. The authors of articles are Latvian and Lithuanian scientists, historians of science and pedagogues. The articles review the lives of graduates, lecturers and employees of Riga Polytechnicum (RP) / Riga Polytechnic Institute (RPI), as well as identify Latvians who lived outside the present territory of Latvia and studied in RPI until the foundation of the Republic of Latvia. The volume contains eight articles.